2020
DOI: 10.1128/aac.01983-19
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of KPC-2-Producing Raoultella ornithinolytica Isolated from a Hospital Wastewater Treatment Plant

Abstract: B acterial carbapenem resistance is a threat to the public health worldwide (1). Klebsiella pneumoniae carbapenemase (KPC) is the most common carbapenemase and can be obtained from carbapenem-resistant Enterobacteriaceae (CRE) that are distributed globally (2, 3). Although bla KPC genes are usually recovered from samples from patients and healthy humans, transmission of bla KPC genes between environmental isolates remains largely unknown (4). In this study, we isolated Raoultella ornithinolytica SRo1810 carryi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
(2 reference statements)
0
5
1
Order By: Relevance
“…This explains why carbapenemase studies on aquatic sources (rivers, lakes, and wastewater treatment plants), livestock, and wildlife are accumulating. For example, hospital wastewater treatment plants in China were shown to contain KPC-2-producing Raoultella ornithinolytica [270], which is an aquatic Gram-negative organism with emerging importance in hospital infections associated with invasive procedures [271]. According to a Swiss study in 2019, the environmental Gram-negative organism Zhongshania aliphaticivorans, which lives in marine sediments, was shown to produce ZHO-1.…”
Section: Other Gram-negative Organismsmentioning
confidence: 99%
See 1 more Smart Citation
“…This explains why carbapenemase studies on aquatic sources (rivers, lakes, and wastewater treatment plants), livestock, and wildlife are accumulating. For example, hospital wastewater treatment plants in China were shown to contain KPC-2-producing Raoultella ornithinolytica [270], which is an aquatic Gram-negative organism with emerging importance in hospital infections associated with invasive procedures [271]. According to a Swiss study in 2019, the environmental Gram-negative organism Zhongshania aliphaticivorans, which lives in marine sediments, was shown to produce ZHO-1.…”
Section: Other Gram-negative Organismsmentioning
confidence: 99%
“…Xin et al reported pollution of estuarine water with bacterial genera including Rheinheimera, Stenotrophomonas, Shewanella, Raoultella, Vibrio, Pseudoalteromonas, Algoriphagus, Bowmanella, and Thalassospira, which all harbor bla OXA-58 [155] conferring resistance to carbapenems and penicillin and an ability to hydrolyze cefpirome and cephalothin but not ceftazidime, cefotaxime, or cefepime. Citrobacter freundii OXA-204 [171] Hospital wastewater E. coli KPC-2 [64] Raoltella ornitholitica KPC-2 [270] Acinetobacter towneri OXA-58 [154] Coastal water A. towneri OXA-58 [155] Municipal water Acinetobacter lwoffii OXA-235 and OXA-278 [163] River water Klebsiella pneumoniae KPC-2 [216] Estuarine water…”
Section: Other Gram-negative Organismsmentioning
confidence: 99%
“…Genes encoding a small multidrug resistance (SMR) efflux transporter were also found in the MRR, which were deduced to be associated with the efflux system ( Kazama et al, 1998 ; Shen et al, 2021 ). Furthermore, both pK433-NDM and pFAHZZU2447_NDM lacked a tra module, which encodes a primary pilus for conjugation ( Chi et al, 2020 ). In addition, the OriTFinder results indicated that pFAHZZU2447_NDM had incomplete conjugative modules with the absence of a transfer site ( oriT ) and type IV coupling protein (T4CP) ( Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The number and size of plasmids in K. pneumoniae 5589 were detected by S1-PFGE of total DNA (Chi et al, 2020). The locations of plasmids harboring the bla OXA-181 and mcr-8 were determined by Southern blotting and hybridization with digoxigenin-labeled specific probes.…”
Section: Plasmid Analysis and Conjugation Assaymentioning
confidence: 99%